Who we are? - Saibal Das (Imaging Journal of Clinical and Medical Sciences - Peertechz Publications, 2014)
It's my privilege and honor to write the editorial of a newly enterprising title "Imaging Journal of Clinical and Medical Sciences (IJCMS)." "Peertechz" has done an excellent work again. We are already enamored by an overwhelming response from various authors throughout the globe. Again I will say it's just the beginning of a new endeavor. IJCMS is a peer-reviewed international journal, with the main purpose to provide a scientific platform for the publication of papers documenting recent advances and new developments in the field of radiology in medicine and biology, as well as regularly updating on existing modalities and scenarios.